A35 MICROBIAL PROTEOLYTIC SIGNATURE IN ULCERATIVE COLITIS INDUCES AN INFLAMMATORY SIGNATURE IN MICROBIOTA-HUMANIZED MICE - Galipeau, H J; Turpin, W; Caminero Fernandez, A; Santiago, A; Libertucci, J; Bermudez-Brito, M; Armstrong, S; Bedrani, L; Croitoru, K; Verdu, E (Journal of the Canadian Association of Gastroenterology, 2020)
BackgroundAltered gut microbiota composition has been associated with inflammatory bowel diseases (IBD) including ulcerative colitis (UC), but causality and bacterially-driven mechanisms, are unclear. Proteases within the gastrointestinal tract play a critical role in maintaining homeostasis and are tightly regulated by anti-proteases. Host-derived proteolytic imbalances have been described in IBD, including UC, however, the role of intestinal microbiota as a source of proteases and anti-proteases has largely been ignored.AimsTo study microbial proteolytic activity and intestinal microbiota profiles in a cohort of individuals at-risk for IBD, and in those individuals that develop UC at follow-up.MethodsFecal samples were collected from healthy individuals at-risk for IBD and who went on to develop UC (pre-UC; n=14) and again after UC diagnosis (post-UC, n=10). Fecal samples from matched at-risk individuals that did not develop UC were used as healthy controls (n=52). Overall fecal proteolytic and elastolytic activity was measured. We performed metagenomics sequencing in 4 UC subjects (pre and post) and 4 matched HC using Illumina Hi-Seq from stool DNA. To investigate bacterial origin and functional significance, pregnant germ-free (GF) mice were colonized with a fecal sample from a selected UC subject (pre and post) and a matched HC. Naturally colonized litters were followed for 12 weeks, after which proteolytic activities and signs of inflammation were measured.ResultsFecal proteolytic and elastase activity was increased in pre- and post-UC samples compared to HCs. Metagenomics revealed over 20k genes were significantly different between HC and pre-UC samples, and of these, 440 related to proteases and peptidases. Increased fecal proteolytic activity, higher lipocalin levels, and increased colonic polymorphonuclear cells in colonic H&E sections was observed in pre- and post-UC colonized mice compared to HC colonized mice. Mice colonized with pre-UC microbiota showed increased mRNA expression of genes linked to immunological disease, antimicrobial and inflammatory responses (ie. Tlr2, Tlr5, Nod2, and Il1b) as compared to HC colonized mice.ConclusionsThese results suggest increased fecal proteolytic activity is observed prior to the onset and clinical diagnosis of UC in patients at-risk for IBD, and upon transfer to mice born from colonized GF dams, low-grade inflammation develops. These pathways could be developed as novel non-invasive biomarkers to monitor at-risk populations. Submitted on behalf of the CCC-GEM Project consortium. Supported by CCC GIA to EF VerduFunding AgenciesCCC